An assessment of sensitivity to change of the Oral Health Impact Profile in a clinical trial - Allen PF, McMillan AS, Locker D (Blackwell Synergy, 2001)
Patient-based assessment of oral health outcomes is of growing interest. Measurement of change following clinical intervention is a key property of a health status measure. To date, most of the research on oral health status measurement has focused on construct and discriminant validity of health status measures